Analisis Indikator Moneter Terhadap Pertumbuhan Ekonomi Di Indonesia - Dewi Mahrani Rangkuty; Mohammad Yusuf; Rusiadi Rusiadi; Bakhtiar Efendi; Putri Subakti (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The purpose of this study is to determine the relationship between inflation, interest rates, money supply, and exchange rates on economic growth in Indonesia in the short, medium, and long term. By using an associative/quantitative research approach and secondary data. Data collection techniques are used by means of documentation studies. The method used in this study is Vector Autoregression. The results show that in the short run economic growth is responded to positively by inflation. In the medium term, the inflation variable is responded negatively by economic growth and returns to equilibrium in the long run. The results of variance decomposition show that the variable of economic growth is influenced by the variable itself in the short, and long term. The government, Bank Indonesia is advised to stabilize the inflation rate by implementing an expansionary monetary policy.